1987
DOI: 10.1128/jvi.61.8.2351-2361.1987
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular digestion of reovirus particles requires a low pH and is an essential step in the viral infectious cycle

Abstract: Lysosomotropic drugs such as NH4Cl have been useful for studying the role of low pH in early events in virus infection. NH4Cl blocks the production of infectious progeny virus in mammalian reovirus-infected cells. The inhibitory effect of NH4C1 is mediated by an inhibition of intracellular digestion of reovirus outer capsid proteins. In vitro digestion of viral outer capsid proteins produces infectious partially uncoated particles, called intermediate subviral particles, which are no longer inhibited by the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
224
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(232 citation statements)
references
References 48 publications
7
224
1
Order By: Relevance
“…Infection by reovirus requires the disassembly of its outermost capsid in order to penetrate the host and initiate viral gene transcription. [9][10][11] Second, we found that ISVPs efficiently infected "reovirus-resistant" cells. Golden et al also found that the addition of proteases to the media of resistant cells rendered them susceptible to infection.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Infection by reovirus requires the disassembly of its outermost capsid in order to penetrate the host and initiate viral gene transcription. [9][10][11] Second, we found that ISVPs efficiently infected "reovirus-resistant" cells. Golden et al also found that the addition of proteases to the media of resistant cells rendered them susceptible to infection.…”
Section: Discussionmentioning
confidence: 70%
“…to perforate either the endosomal/lysosomal or the plasma membrane and thus to penetrate the cytoplasm. [9][10][11] In order to do this, we labeled reovirus with Cy3-maleimide monofunctional dye and exposed resistant and susceptible cells grown on glass slides to this labeled reovirus. Immunofluorescence was then performed to detect lysosomal associated membrane protein 2, frequently used as a functional marker of lysosomes.…”
Section: In Resistant Cell Lines Reovirus Binds Accumulates Within mentioning
confidence: 99%
See 2 more Smart Citations
“…Most evidence indicates that the majority of naked animal virus particles follow the receptor-mediated endocytosis pathway to infect cells (Marsh and Helenius, 1989). Whether some of these viruses need a low pH step to trigger the crossing of the endosomal membrane, or enter cells by a pH-independent mechanism, remains open to debate (Brown and Burlingham, 1973;Madshus et al, 1984c;Svensson, 1985;Sturzenbecker et al, 1987;Gromeier and Wetz, 1990;Kronenberger et al, 1991;Varga et al, 1991). Two major questions, therefore, remain to be answered with respect to the mechanism of picornavirus entry into cells: Is a given picornavirus species internalized through endosomes in a particular cell type?, or do endosomes need to be acidified for the virus to enter cells?…”
Section: Entry and Uncoating Of Picornavirusesmentioning
confidence: 99%